Possibilidades do ensino das lutas na escola: uma pesquisa-ação com professores de educação física - Bernhardt Hegele; Fernando Jaime González; Robson Machado Borges (Universidade Estadual do Oeste do Paraná, 2018)
This research sought to verify the consequences of a collaborative training experience, in the conceptions of teachers about the approach of the struggles in the School Physical Education classes. For that, it was operated methodologically with the accomplishment of an action research with four physical education teachers who work in public schools in the interior of Rio Grande do Sul (Brazil). The teachers, together with one of the researchers, constituted a study group that met weekly in eight meetings, in order to reflect on the approach of the struggles in physical school education. The results indicate that, initially, the teachers did not feel able to thematize the struggles in the school. Especially, because they did not have a specific curricular component in their initial formation. However, after the study, teachers understood that it is possible to work with the struggles in physical education classes. The main factors that led to this change were the study of the games of fights and their classification based on distances, the production of tasks during the meetings and the corporal experience in the meetings.